2021
DOI: 10.1007/s10753-021-01523-x
|View full text |Cite
|
Sign up to set email alerts
|

Stellate Ganglion Block Improves the Proliferation and Function of Splenic CD4 + T Cells Through Inhibition of Posthemorrhagic Shock Mesenteric Lymph–Mediated Autophagy

Abstract: Background and objectiveSevere hemorrhagic shock leads to excessive in ammation and immune dysfunction, which resulted in high mortality related to mesenteric lymph return. Recent study showed that stellate ganglion block (SGB) increased survival rate in rats suffered hemorrhagic shock. However, whether SGB ameliorates immune dysfunction induced by hemorrhagic shock, it remains unknown. The aim of present study is therefore to verify the favorable effect of SGB on the proliferation and function of splenic CD4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…CRP in group S was significantly lower than that in group N on the sixth day after surgery, and there was no statistical difference when IL-6 reached its peak, which may be related to factors such as the longer delay difference in CRP change and the effect of liver resection on liver release of CRP. In terms of the inflammatory response, Ying Li et al found that stellate ganglion block could increase CD4 + T cell activity and decreased IL-2, IL-4, and TNF- stimulated TIPE2 production, hence increasing rat survival after severe hemorrhagic shock [ 6 ]. In 2020, Eugene Lipov et al put forward a hypothesis and gave some evidence to show that stellate ganglion block may regulate immune inflammation by regulating sympathetic innervation of primary (thymus, bone marrow) and secondary immune organs (such as the spleen, lymph nodes, and mucosa-associated lymphoid tissues), and it finally inhibits the production of pro-inflammatory cytokines (like IL-1, IL-6, TNF-α, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…CRP in group S was significantly lower than that in group N on the sixth day after surgery, and there was no statistical difference when IL-6 reached its peak, which may be related to factors such as the longer delay difference in CRP change and the effect of liver resection on liver release of CRP. In terms of the inflammatory response, Ying Li et al found that stellate ganglion block could increase CD4 + T cell activity and decreased IL-2, IL-4, and TNF- stimulated TIPE2 production, hence increasing rat survival after severe hemorrhagic shock [ 6 ]. In 2020, Eugene Lipov et al put forward a hypothesis and gave some evidence to show that stellate ganglion block may regulate immune inflammation by regulating sympathetic innervation of primary (thymus, bone marrow) and secondary immune organs (such as the spleen, lymph nodes, and mucosa-associated lymphoid tissues), and it finally inhibits the production of pro-inflammatory cytokines (like IL-1, IL-6, TNF-α, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The surgery was carried out under inhalation anesthesia in all rats as previous described (20,21). After surgical procedures, the inhalation anesthesia was removed.…”
Section: Acute Hemorrhage and Various Treatments In Conscious Ratsmentioning
confidence: 99%
“…Previous studies have shown that stellate ganglion block (SGB), a standard method of blocking sympathetic nerves, can reduce intestinal barrier dysfunction and prolong the survival time in the HS rat model ( 159 ). The latest research shows that SGB administration significantly normalized the population of CD4 + T cells and the level of IL-2, IL-4, and TNFα-induced protein 8 like 2 (TIPE2) in the development of HS ( 146 ).…”
Section: New Insights Into Hs Therapeutics With Innate Immune Regulationmentioning
confidence: 99%